Impacts of natural fractures on acid fracture design: A modeling study. (November 2020) - Aljawad, Murtada Saleh; Schwalbert, Mateus Palharini; Mahmoud, Mohamed; Sultan, Abdullah
Abstract: Carbonate formations, which are usually naturally fractured, are good candidates for acid fracturing. Natural fractures have a significant impact on the execution and outcomes of acid fracture design. The interaction of hydraulics with natural fractures can be complex and is rarely considered in acid fracture modeling. This study provides an integrated approach where natural fractures are considered in both acid fracture and productivity modeling. The model is dynamic, integrating fracture propagation with reactive acid transport and coupled with heat transfer. The proposed acid fracture model generates fracture network permeability, which is then used in the productivity model. A parametric study was conducted to investigate the impact of natural fractures on the productivity of acid fractured wells. Multiple scenarios of different natural fracture spacings, lengths, and widths were investigated. It was determined that the existence of natural fractures negatively impacted productivity because they limited the extension of the hydraulic fracture. The impact was found to be more significant when the reservoir was tight, situations where a long hydraulic fracture is desirable. It was also found that the optimum acid injection rate increased with an increase in natural fracture intensity at moderate reservoir permeability levels. Nevertheless, the maximum injection rate should be targeted in tight formations, no matter the intensity of the natural fracture. Implementation of diversion stages could significantly improve the productivity of an acid fractured well.